African Bioethics vs. Healthcare Ethics in Africa: A Critique of Godfrey Tangwa. Issue 2 (24th April 2015) - Fayemi, Ademola K.
Abstract: It is nearly two decades now since the publication of Godfrey Tangwa's article, 'Bioethics: African Perspective', without a critical review. His article is important because sequel to its publication in Bioethics, the idea of 'African bioethics' started gaining some attention in the international bioethics literature. This paper breaks this relative silence by critically examining Tangwa's claim on the existence of African bioethics. Employing conceptual and critical methods, this paper argues that Tangwa's account of African bioethics has some conceptual, methodic and substantive difficulties, which altogether do not justify the idea of African bioethics, at least for now. Contra Tangwa, this article establishes that while African bioethics remains a future possibility, it is more cogent that current efforts in the name of 'African bioethics' be primarily re‐intensified towards 'Healthcare ethics in Africa'.